Analysis of Variation Characteristics of the Annual Maximum Flood Flow of Main Streams in Guangdong Province - LIANG Yuanyuan (Renmin Zhujiang)
In order to understand the variation characteristics of the annual maximum flood flow at the main hydrological stations in Guangdong province and reduce the production,living,and ecological environment problems caused by floods,the annual maximum flood flow series from 1977 to 2014 at seven hydrological stations in Guangdong province,namely,Sanshui Station,Makou Station,Gaoyao Station,Shijiao Station,Boluo Station,Huazhou Station,and Chaoan Station,are studied.MK test and Pettitt test are used to carry out study or wavelet analysis on the characteristics of the trend,variability,and cycle changes of the annual maximum flood flow at typical stations in the main streams of Guangdong province.The results show that:① the annual maximum flood flow at Boluo Station and Chaoan Station decreases slightly,while that at the other five stations increases,with that at Shijiao Station and Sanshui Station rising significantly.② Four of the seven stations have variability,and they are Gaoyao Station (in 1991 and 1992),Shijiao Station (in 1992,2011,and 2012),Makou Station (in 1993),and Sanshui Station (in 1993),and the variability occurs more than once at Gaoyao and Shijiao stations.In terms of spatial and temporal distribution,the four stations with variability mostly belong to the Xijiang and Beijiang river systems in the 1980s,1990s,and the 21st century.③ Sanshui Station has two main cycles of 2~10 a and 20~30 a,and Makou Station has cycles of 2~9 a and 9~27 a.Gaoyao Station experiences a cycle of 4~10 a and 10~24 a,and Shijiao Station owns a cycle of 2~12 a and 12~20 a.Boluo Station has a cycle of 5~12 a and 12~24 a.In addition,Huazhou Station experiences three cycles of 3~7 a,7~18 a,and 18~26 a,and Chaoan Station experiences cycles of 3~10 a,10~14 a,and 14~23 a,respectively.